Comparison of Eclipse Smart Segmentation and MIM Atlas Segment for liver delineation for yttrium‐90 selective internal radiation therapy. Issue 8 (15th June 2022) - Li, Jun; Anne, Rani
Abstract: Purpose: The aim was to compare Smart Segmentation of Eclipse treatment planning system and Atlas Segment of MIM software for liver delineation for resin yttrium‐90 (Y‐90) procedures. Materials and methods: CT images of 20 patients treated with resin Y‐90 selective internal radiation therapy (SIRT) were tested. Liver contours generated with Smart Segmentation and Atlas Segment were compared with physician manually delineated contours. Dice similarity coefficient (DSC), mean distance to agreement (MDA), and ratio of volume (RV) were calculated. The contours were evaluated with activity calculations and ratio of activity (RA) was calculated. Results: Mean DSCs were 0.77 and 0.83, MDAs were 0.88 and 0.71 cm, mean RVs were 0.95 and 1.02, and mean RAs were 1.00 and 1.00, for Eclipse and MIM results, respectively. Conclusion: MIM outperformed Eclipse in both DSC and MDA, whereas the differences in liver volumes and calculated activities were statistically insignificant between the Eclipse and MIM results. Both auto‐segmentation tools can be used to generate initial liver contours for resin Y‐90 SIRT, which need to be reviewed and edited by physicians.